Say-on-Pay in the UK Financial Sector: The Impact of the Media and Institutional Shareholders on Voting behaviour - Pringle, James (2013)
The debate surrounding the Say-on-Pay regulatory policies introduced in the UK in 2002 has been plagued by mixed evidence and a lack of focus. With the increased amount of criticism and scrutiny regarding CEO pay packages, particularly in the financial sector following the global financial crisis, the issue of shareholder activism has become a hot topic. This quantitative study attempts to provide further evidence in the debate over whether Say-on-Pay is effective, but also attempts to add a new dimension to the debate by analysing the role of the media and of institutional shareholders on shareholder voting patterns. These are elements that have been strangely absent in the literature for Say-on-Pay so far. Both simple statistical analysis and regression analysis are conducted on voting and CEO pay data from 2002 to 2005 for the UK financial sector. The results show that neither the media nor the presence of institutional shareholders have any impact on the voting behaviour of shareholders; and overall Say-on-Pay is ineffective, because the level of dissonant votes has no bearing on the CEOs earnings one year following the vote, indeed CEO pay actually increased from 2002 to 2005 on average.